Peranan Plasma Nutfah Padi dalam Meningkatkan Produktivitas Lahan Keracunan Besi - Tintin Suhartini (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
Productivity of land in Java insel decreased. Therefore, it is necessary to utilize marginal Fe toxic land in order to increase production of rice. One of the hinderness is the lack of rice variety which is tolerant to this condition. The rice research institute and Balitbio in Bogor have the collection of rice varieties which can be used in breeding program. The program obtained a rice variety that is adaptive to Fe toxic land. Key words: Rice, Iron